1992
DOI: 10.1002/nur.4770150109
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing staff nurse job performance and achievements

Abstract: While recognition for work has been positively related to nurses' job satisfaction in the research literature, specific types of recognition that would be most meaningful have not been identified. In this descriptive survey, 341 randomly selected staff nurses rated the extent of meaningfulness of 38 head nurse recognition behaviors. The most meaningful, in order of importance, were monetary rewards commensurate with performance, private verbal feedback, and written acknowledgment. Three other categories of rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 24 publications
(13 reference statements)
3
59
1
3
Order By: Relevance
“…However, this is higher than in previous research [22]. This study also showed that being appreciated for high performance was most important to job satisfaction of non-physician staff [22].…”
Section: Discussioncontrasting
confidence: 64%
“…However, this is higher than in previous research [22]. This study also showed that being appreciated for high performance was most important to job satisfaction of non-physician staff [22].…”
Section: Discussioncontrasting
confidence: 64%
“…Financial recognition may serve as an incentive in retaining these RN. The higher salary may have boosted these RNs' sense of self‐worth, given that pay was often associated with one's status in the organisation ( Blegen et al , 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…Promotion within an organization can take the form of career ladders and career advancement programs (Aiken et al, 2001); or promotion of nurses to leadership positions such as preceptors, mentors, supervisors, or expert speakers (Blegen et al, 1992). Educational advancement opportunities include organizations' educational offerings or financial support for advancing nurses' education outside the organization.…”
Section: Literaturementioning
confidence: 99%
“…Recognition takes the form of a formal employee recognition program and is a show of appreciation for staff nurse performance and achievement (Blegen et al, 1992). Successful recognition programs convey a feeling of respect for staff (Osborne, 2004;Tang, 2003).…”
Section: Literaturementioning
confidence: 99%